Theology of science: Its collocation and critical role for understanding of limits of theological and scientific investigations - Sierotowicz, Tadeusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
The paper presents a brief outline of Michał Heller’s programme of theology of science, with specific attention to its collocation and critical role with respect to both theology and science. The former consideration is based on a third domain of truths (Hans Urs von Balthasar), while the latter is inspired by Józef Tischner’s presentation of religious thinking. Theology of science as such will be described with reference to Larry Laudan’s approach, considered here as a very useful and pragmatic tool for the description of basic concepts of this theology.
Keywords: theology of science; third domain of the truths; research tradition; Michał Heller; Hans Urs von Balthasar; Józef Tischner; Larry Laudan